Quality Assurance in Islamic Higher Education (Case in UIN Sunan Gunung Djati Bandung) - Elis Ratna Wulan; Dindin Djamaluddin (AIUA Journal of Islamic Education, 2019)
The main goal of this research is to identify student satisfaction factor on academicand learning processes in Islamic higher education and the degree of this satisfaction. It is believed that academic and learning satisfaction is one of the important factors for the quality assurance in Islamic higher education. The population of this study in particular includes UIN Sunan Gunung Djati Bandung student, which is one of the Indonesia public universities and considered the students from 2016 to 2018. A questionnaire was given to a group of students as respondent. Based on this, the degree of satisfaction and the factors affecting it were investigated and identified. Descriptive statistics was used to identify the quality assurance aspect. The result showed that six aspects has the high validity in determining the quality assurance in Islamic higher education.